Ionic-Liquid-Functionalized Graphene Nanoribbons for Anion Exchange Membrane Fuel Cells. Issue 4 (7th March 2017) - Liu, Xundao; Chen, Xiaohong; Hu, Yong; Gong, Tianle; Li, Hong; Zhang, Yongming
Abstract : Ionic-liquid-functionalized graphene nanoribbons (IGNRs) were synthesized, and a novel composite anion exchange membrane (AEM) was then constructed by blending the IGNRs with an ionic-liquid-functionalized perfluorinated anion polymer (I-PFSO2 NH2 -Cl) in solution, followed by solution casting and anion exchange. FT-IR, NMR, SEM and Raman spectra were applied to analyze the chemical composition and morphology of the composite AEM, confirming their successful synthesis. The composite AEM containing 1.0% IGNRs displayed the highest conductivity of 120.5 mS.cm −1 at 80°C in water, which was 1.7 times higher than that of the pristine membrane. Meanwhile, a new IGNRs/Pt electrocatalyst structure that uses IGNRs as the supporting material was prepared to improve the compatibility between the fillers and the Pt catalyst, and it was effectively used in the anion exchange membrane fuel cell (AEMFC). The single cell of the composite AEM with the IGNRs/Pt electrocatalysts reached a peak power density of 197.2 mW cm −2, which was 1.9 times higher than that of the pristine membrane. Thus, the IGNRs architecture appears to be a promising candidate for membrane fillers and electrocatalyst support materials to enhance the performance of AEMFCs.